2012
DOI: 10.1271/bbb.110968
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Modified Arabinoxylan from Rice Bran (MGN-3) onD-Galactosamine-Induced IL-18 Expression and Hepatitis in Rats

Abstract: We investigated in this study the effect of modified arabinoxylan from rice bran (MGN-3) and its fractions on D-galactosamine (D-GalN)-induced IL-18 expression and hepatitis in rats. Male Wistar rats were pretreated with MGN-3 or fractions of the MGN-3 hydrolysate, or with saline 1 h before administering D-GalN (400 mg/kg B.W.). The serum transaminase activities, IL-18 mRNA expression level in the liver and IL-18 concentration in the serum were determined 24 h after injecting D-GalN. Both the oral and intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…MGN-3 was hydrolyzed with HCl at 100°C, and then the hydrolysate treated with cation or anion exchange resin was fractionated by molecular weight (high molecular weight fraction (≥2,000,000 Da), medium molecular weight fraction (2,000,000-400 Da), and low molecular weight fraction (LMW; ≤400 Da)). We concluded that LMW has a stronger hepato-protective effect than MGN-3 [12]. The molecular weight of LMW was measured by ESIMS, and an intense peak at m/z 409 was observed [12].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…MGN-3 was hydrolyzed with HCl at 100°C, and then the hydrolysate treated with cation or anion exchange resin was fractionated by molecular weight (high molecular weight fraction (≥2,000,000 Da), medium molecular weight fraction (2,000,000-400 Da), and low molecular weight fraction (LMW; ≤400 Da)). We concluded that LMW has a stronger hepato-protective effect than MGN-3 [12]. The molecular weight of LMW was measured by ESIMS, and an intense peak at m/z 409 was observed [12].…”
Section: Introductionmentioning
confidence: 82%
“…We concluded that LMW has a stronger hepato-protective effect than MGN-3 [12]. The molecular weight of LMW was measured by ESIMS, and an intense peak at m/z 409 was observed [12]. LMW is a mixture of monosaccharide and oligosaccharides, constituted by glucose as the main component (glucose, 22.8%; mannose, 1.5%; galactose, 0.5%; arabinose, 0.3%; protein, 2.85%) [12].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations